Sources, supply, and seasonality of total suspended matter and associated organic carbon and total nitrogen in three large Asian rivers—Ganges, Mekong, and Yellow - Sarkar, Siddhartha; Verma, Sangeeta; Begum, Most Shirina; Park, Ji-Hyung; Kumar, Sanjeev (Frontiers in Earth Science, 2023)
Asian rivers, covering ~29 % of the global river surface area, account for ~ 35 % of the global freshwater discharge and transport a disproportionately large flux (~70 %) of total suspended matter to the oceans. With recent anthropogenic and climate-induced changes in the flow regimes, it is challenging to constrain the fluxes and elemental signatures of the suspended organic matter in rivers. This study aimed to understand seasonal changes in the characteristics of total suspended matter (TSM) associated organic carbon (C) and total nitrogen (N) during high and low flow periods in three large Asian rivers (Ganges, Mekong, and Yellow). By measuring organic C and total N contents and their isotopic compositions at multiple locations along the studied rivers, distinct seasonality in the sources of organic matter was observed. Allochthonous sources dominated the organic matter pool during the high flow condition, whereas autochthonous organic matter derived from enhanced phytoplankton production appeared to have dominated during low flow. C/N ratio showed positive correlation with altitude during wet period, which reversed during dry, supporting the transition of sediment dominated high flow riverine system into relatively clear and productive low flow system. Generally, organic matter content in TSM was higher during the low flow with signatures of potential N2 fixation. Temporal analysis based on present and earlier estimates of fluxes and yields of TSM indicated manifold decrease in TSM load and associated C and N fluxes over decades in the three river systems largely attributed to reduction in river discharge. Wastewater dominated locations showed similar C and N contents and isotopic signatures as those of productive river waters during low flow, indicating a possible interference in the interpretation of biogeochemical information.